Faktor Determinan Yang Memperngaruhi Pemilihan Tempat Ibu Bersalin Di Jawa Tengah (Analisis Data SDKI Tahun 2017) - Wibowo, Syifa Sofia; Kurniadi, Arif (POLTEKKES KEMENKES MANADO, 2024)
Background: The maternal mortality rate in Indonesia was three times higher than the MDG objective, according to the 2015 data. In order to accelerate the decrease in the MMR, efforts are made to guarantee that all mothers have access to high-quality maternal health services. In 2020, Indonesian healthcare facilities indication of assisted births by medical professionals fell short of the 2020 RENSTRA (Strategic Planning) target, which was 86% instead of 87%. Objective: This study aims to examine four aspects that may affect a pregnant woman's decision about the place of delivery: the economic status, their level of education, the place of living, and the availability of health insurance. Methods: This study used data from the 2017 Indonesian Demographic Health Survey (DHS) Program. The study design employed was cross-sectional. The method of sampling employed in this study was total random sampling, consist of 1.058 data. This study's univariate analysis utilized the frequency test, and its bivariate analysis employed the Pearson product moment test. Results: The economic status of the family, the mother's level of education and their ownership of health insurance are risk factors that may affect the place of delivery that mothers choose, but type of residence is not. The largest contributing factor to mortality among mothers and babies in Central Java may be family economic problems. Ensuring everyone has access to proper health insurance, particularly those with modest incomes, can help to solve this issue. Conclusion: Family economy, maternal education, and health insurance influence the choice of childbirth location and maternal-infant mortality.